Analysing the Requirements of a Binding Sale and Purchase Agreement and its Implementation in Property Companies in Indonesia - Yetmiaty, Yetmiaty; Rasji, Rasji (Dinasti Research, 2024)
This article is entitled analysis of the requirements of the sale and purchase binding agreement and its implementation in property companies in Indonesia, using the research method of empirical normative legal approach. The results of this study indicate that the implementation of Government Regulation number 12 of 2021 concerning the requirements of the Sales and Purchase Agreement system requirements is not very effective when applied to Indonesian Property Companies, especially if Property Companies or Development Actors use the Pre Project Selling concept, where in this concept, development actors can sell or market before the property product is built or the licensing requirements have not been fulfilled which results in Article 22 paragraph (5) regarding the requirements of the PPJB system cannot be in accordance with the practices that occur in the property business world in Indonesia.